Comparison between online shopping and mall shopping / Dania Sharmaine Badiango Abdullah, Mansur Beddu and Ross Shayana Shamsur - Badiango Abdullah, Dania Sharmaine; Beddu, Mansur; Shamsur, Ross Shayana (2010)
The shift from physical (brick and mortar) stores and hard copy catalog stores toward electronic stores (e-tailing) may be seen as a continuous innovation building on past changes brought about by in-home shopping methods such as catalog, TV and direct mail. In this paper, we have examined the influence of customers characteristics on perception of shopping benefits associated with electronic and physical shopping. The empirical study finds the two shopping formats to be clearly different from each other in terms of perceived shopping benefits.